New species and new records of predaceous midges in the genera, Schizonyxhelea Clastrier and Stilobezzia Kieffer from Mexico (Diptera: Ceratopogonidae) - Huerta, Herón; Grogan, William L., Jr. (Zootaxa, 2017)
We describe and illustrate new species and provide new records of predaceous midges in the genera, Schizonyxhelea Clastrier and Stilobezzia Kieffer from Mexico (Diptera: Ceratopogonidae). Two new species are described and illustrated: Schizonyxhelea zoologica n. sp., and, Stilobezzia (Acanthohelea) spinellii n. sp. Included are the first Mexican records of Schizonyxhelea forattinii Wirth & Grogan, Stilobezzia (Acanthohelea) fuscula Wirth, S. (Stilobezzia) hirta Borkent and S. (S.) pallidiventris (Malloch). New distribution records are also provided for several other species that were previously known from Mexico, and a key is provided for all species of Schizonyxhelea and Stilobezzia from Mexico.